The Interactions Between Three Typical PPCPs and LDH - Li, Erwei; Liao, Libing; Lv, Guocheng; Li, Zhaohui; Yang, Chengxue; Lu, Yanan (Frontiers in Chemistry, 2018)
With a layered structure, layered double hydroxide (LDH) has potential applications in remediation of anionic contaminants, which has been a hot topic for recent years. In this study, a Cl type Mg-Al hydrotalcite (Cl-LDH) was prepared by a co-precipitation method. The adsorption process of three pharmaceuticals and personal care products (PPCPs) [tetracycline (TC), diclofenac sodium (DF), chloramphenicol (CAP)] by Cl-LDH was investigated by X-ray diffraction (XRD), Zeta potential, dynamic light scattering (DLS), BET, Fourier transform infrared (FTIR) spectroscopy, and molecular dynamics simulation. The results showed that the adsorption equilibrium of TC and DF could be reached in 120 min, and the maximum adsorption capacity of the TC and DF were 1.85 and 0.95 mmol/g, respectively. The isothermal adsorption model of TC was fitted with the Freundlich adsorption model, and the isothermal adsorption model of DF was fitted with the Langmuir adsorption model. The adsorption dynamics of TC and DF followed the pseudo-second-order model. The adsorption mechanisms of the three PPCPs into Cl-LDH were different based on the experimental results and molecular dynamics simulation. The TC adsorption on Cl-LDH was accompanied by the electrostatic interactions between the negative charge of TC and the positive charge of Cl-LDH. The uptake of DF was attributed to anion exchange and electrostatic interaction. Cl-LDH does not adsorb CAP due to no electrostatic interaction. The molecular dynamic simulation further confirmed different configurations of three selected PPCPs, which were ultimately responsible for the uptake of PPCPs on Cl-LDH.